ANALISIS KOMPREHENSIF METODOLOGI DAN KONTESTASI PEMIKIRAN DALAM KITAB SHAFWATUT TAFAASIR KARYA MUHAMMAD ALI ASH-SHAABUUNY DAN AL-WASITH KARYA MUHAMMAD SAYYID AL-THANTHAWI - Sugiro Abdillah; Ahmad Fauzan Maulidan; Akhmad Dasuki (JURNAL ILMIAH NUSANTARA, 2026)
This study analyzes the methodology of interpretation and contestation of thought in two major works: Muhammad 'Ali ash-Shabuni's Shafwatut Tafāsīr and Muhammad Sayyid Tantawi's Tafsīr al-Wasīṭ. The background of this study is an effort to bridge the classical tafsir heritage with the social and intellectual demands of modern society. Using a descriptive-comparative qualitative method, the study found that both mufassirs applied the tahlīlī method through the integration of history and ra'yi. However, both have different orientations: Ash-Shabuni emphasizes linguistic aspects, balaghah, and summarizing classical tafsir with a conservative-moderate theological stance. In contrast, Tantawi emphasizes the adabi-ijtima'i approach that is more contextual to contemporary social problems and is brave in performing muamalah ijtihad. The study concludes that these methodological differences are two models of tafsir responses that complement each other and enrich the treasures of Muslim intellectuals in facing the challenges of the times.